The Influence of Serum Uric Acid on the Brain and Cognitive Dysfunction - Mijailovic, Natasa R.; Vesic, Katarina; Borovcanin, Milica M. (Frontiers in Psychiatry, 2022)
Uric acid is commonly known for its bad reputation. However, it has been shown that uric acid may be actively involved in neurotoxicity and/or neuroprotection. These effects could be caused by oxidative stress or inflammatory processes localized in the central nervous system, but also by other somatic diseases or systemic conditions. Our interest was to summarize and link the current data on the possible role of uric acid in cognitive functioning. We also focused on the two putative molecular mechanisms related to the pathological effects of uric acid – oxidative stress and inflammatory processes. The hippocampus is a prominent anatomic localization included in expressing uric acid’s potential impact on cognitive functioning. In neurodegenerative and mental disorders, uric acid could be involved in a variety of ways in etiopathogenesis and clinical presentation. Hyperuricemia is non-specifically observed more frequently in the general population and after various somatic illnesses. There is increasing evidence to support the hypothesis that hyperuricemia may be beneficial for cognitive functioning because of its antioxidant effects but may also be a potential risk factor for cognitive dysfunction, in part because of increased inflammatory activity. In this context, gender specificities must also be considered.